PrEP Awareness and Attitudes in a National Survey of Primary Care Clinicians in the United States, 2009–2015 - Smith, Dawn K.; Mendoza, Maria C. B.; Stryker, Jo Ellen; Rose, Charles E. (PLOS ONE, 2016)
Objectives As trials were assessing the safety and efficacy of daily oral antiretroviral preexposure prophylaxis (PrEP) for the prevention of HIV infection, there was a clear need to understand the evolution of knowledge of, and attitudes toward, PrEP among primary care clinicians. Methods Physicians and nurse practitioners were surveyed in 2009 (n = 1500), 2010 (n = 1504), 2012 (n = 1503), 2013 (n = 1507), 2014 (n = 1508) and 2015 (n = 1501) to assess their awareness of PrEP, willingness to prescribe PrEP, and whether they support use of public funds to pay for PrEP. Pharmacists (n = 251) were surveyed about PrEP in 2012 only. Descriptive statistics were computed for physician demographics and PrEP-related questions. Prevalence ratios for willingness to prescribe PrEP were computed using Poisson regression analysis. Results Awareness of PrEP was low among clinicians (2009: 24%, 2010: 29%) but increased after trials reported effectiveness (2012: 49%, 2013: 51%, 2014: 61%, 2015: 66%). Following a description of PrEP with an estimated effectiveness of 75%, across 6 of the study years 91% of clinicians indicated a willingness to prescribe PrEP to at least one group at high risk of HIV acquisition. A smaller majority of clinicians indicated support for public funding of PrEP in 2009: 59%, 2010: 53%, and 2013: 63%. Conclusions In surveys conducted before and after the release of PrEP trial results, primary care clinicians were largely unaware of PrEP. They indicated high levels of willingness to prescribe it for patients at high risk of HIV acquisition and expressed interest in education about how to deliver this new clinical HIV prevention method. It will be important to continue monitoring clinician knowledge, attitudes, and practices as the use of PrEP increases in the US.